The Epithelial Sodium Channel ?-Subunit: New Notes for an Old Song - Rojas-Montecinos, P (2012)
Amiloride-sensitive epithelial Na_ channels (ENaCs) can be formed by different combinations of four homologous subunits, named ?, ?, ?, and ?. In addition to providing an apical entry pathway for transepithelial Na_ reabsorption in tight epithelia such as the kidney distal tubule and collecting duct, ENaCs are also expressed in nonepithelial cells, where they may play different functional roles. The ?-subunit of ENaC was originally identified in humans and is able to form amiloride-sensitive Na_ channels alone or in combination with ? and ?, generally resembling the canonical kidney ENaC formed by ?, ?, and ?. However, ? differs from ? in its tissue distribution and channel properties. Despite the low sequence conservation between ? and ? (37% identity), their similar functional characteristics provide an excellent model for exploring structural correlates of specific ENaC biophysical and pharmacological properties. Moreover, the study of cellular mechanisms modulating the activity of different ENaC subunit combinations provides an opportunity to gain insight into the regulation of the channel. In this review, we examine the evolution of ENaC genes, channel subunit composition, the distinct functional and pharmacological features that ? confers to ENaC, and how this can be exploited to better understand this ion channel. Finally, we briefly consider possible functional roles of the ENaC ?-subunit. © 2012 the American Physiological Society.